Enhanced self-assembly of the 7–12 sequence of amyloid-β peptide by tyrosine bromination. Issue 4 (2nd April 2020) - Maiolo, Daniele; Pizzi, Andrea; Gori, Alessandro; Bergamaschi, Greta; Pigliacelli, Claudia; Gazzera, Lara; Consonni, Alessandra; Baggi, Fulvio; Moda, Fabio; Baldelli Bombelli, Francesca; Metrangolo, Pierangelo; Resnati, Giuseppe
ABSTRACT: Alzheimer's disease (AD) is a serious neuropathology related to the misfolded assembly state of amyloid-beta (Aβ40 and Aβ42) peptides. It has been demonstrated that protein post-translation modifications (PPTMs) of the more hydrophilic N -term moiety of the Aβ peptide affect its aggregation kinetics and interaction with the environment. Considering that chlorination and bromination are non-canonical PPTMs found in various metabolic pathways and often correlated to inflammatory responses, halogenation of the Y10 of the Aβ N -term could be a putative in vivo modification with implications in the Aβ peptide aggregation propensity. In this framework, we chose as a model system, a short peptide sequence, DSGYEV ( i.e . residues 7–12 of the Aβ N -term) and studied its self-assembly behaviour in comparison to its chlorinated and brominated derivatives. Our results show that Y10 halogenation works as a molecular trigger of the peptide self-assembly in solution, promoting the formation of more structured aggregates. Graphical abstract: